Teaching Self-Care and Hygiene During Puberty for Adolescents with Autism Spectrum Disorders - Sugini, Sugini; Supratiwi, Mahardika; Gunarhadi, Gunarhadi (Angstrom Centre of Education, 2024)
Adolescents with autism spectrum disorders (ASD) have limitations in communication and social interactions caused by the presence of neurobiological disorders. Parents of adolescents of ASD also experience challenging times to discuss puberty, especially in their children’s sexual development, masturbation, self-care and hygiene, and other important sexuality-related topics. However, adolescents with ASD have the right to be treated with respect and to learn information about sexuality education in order to be able to take good care of themselves. The purpose of this article is to discuss puberty and how to teach self-care and hygiene in adolescents with ASD. Based on the literature studies, self-care and hygiene teaching methods that can be provided by parents and teachers, including through social narratives, visual support, social stories, and video modelling. It is expected that teachers and parents can provide appropriate learning methods for adolescents with ASD, so that they can develop daily living activities especially in caring for themselves when going through puberty.